EGG PRODUCTION AND EGG QUALITY TRAITS IN RAJASRI BIRDS REARED UNDER SCAVENGING AND OTHER SYSTEMS OF MANAGEMENT - S.QUDRATULLAH, V.CHINNI PREETAM, V. RAVINDER REDDY, SRINIVAS GURRAM AND (The Journal of Research, PJTSAU, 2019)
A study was conducted to evaluate the growth and production performance of Rajasri, a synthetic backyard bird during growing and laying period. The birds were reared under different systems of management and feeding regimens, ad lib feeding group (T1) reared under intensive system while 20% of ad lib (T2) and 40% of ad lib (T3) groups were reared under semi-intensive condition and T4 group was reared under scavenging at farmers backyard. The results revealed that the body weight gain was significantly (P